PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MATERI POKOK ATURAN SINUS DAN COSINUS PADA SISWA KELAS X SMA NEGERI 1 ENDE TAHUN PELAJARAN 2015/2016 - Marselinus Mbete (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2018)
Learning model that prioritizes activity of students is one type of cooperative learning model of NHT. The type of research used in this study is an experimental research that begins by designing learning tools such as lesson plan, student worksheets and research instruments such us achievement test. Source of data in this study were obtained from tests of student learning outcomes in the form of pretest and posttest. The research approach used is a quantitative approach. The analysis technique used is the analysis of covariance. The results showed that the learning device that is generated for the material rules of sines and cosines corresponding syntax NTH type cooperative learning in this study rate good (to qualify the validity, reliability and sensitivity) of the results of statistical analysis of covariance obtained F count = 9,618182 and F table = 4,11 with numerator degrees of freedom = 1 and degrees of freedom denominator = 37. This case shows that the NHT type cooperative learning can improve learning outcomes math materials sines and cosines rule in grade X SMA Negeri 1 Ende of the scool year 2016/2016.